THE THE ROLE OF THE STATE IN FOSTERING RELIGIOUS HARMONY IN INDONESIA: A HISTORICAL REVIEW, CHALLENGES, AND POLICY TOWARDS MODERATION - Hidayah, Alfina; Rizky Fauziyah, Nadia; Wibowo, Waskito (UIN Raden Mas Said Surakarta, 2024)
This article explores the concept of moderation held by the State through the program run by the Ministry of Religious Affairs named Moderasi Beragama (Religious Moderation). The discussion consists of religious moderation throughout history of Indonesia, highlighted it as a moderate approach supported and organised by the state, including its strategies and challenges. This qualitative research uses content analysis as an analytical method of collecting data from primary and secondary sources. The study showed that Religious Moderation was campaigned by the State through several programs, strategies and a similar proposed agenda started even from the New Order era to the disruption era. Constructed by the multi-religious theological concept of moderation and strengthened by the State constitutional basis, the program met challenges that should develop some strategies to implement religious moderation effectively and efficiently. Although radicalism has not been completely eradicated, at least the state has committed to fostering religious harmony and moderation through inclusive state policies and collaborative efforts with various religious and community stakeholders.